Lynx spiders from Xishuangbanna, Yunnan, China (Araneae: Oxyopidae) - Tang, Guo; Li, Shuqiang (Zootaxa, 2012)
The lynx spiders (Araneae: Oxyopidae) from the tropical forests of Xishuangbanna, Yunnan Province, China were studied. Atotal of three genera and 16 species were examined and studied, including 10 new species from two genera: Hamataliwa fove-ata sp. nov., H. manca sp. nov., H. menglunensis sp. nov., H. oculata sp. nov., H. pedicula sp. nov., H. pentagona sp. nov., H.pilulifera sp. nov., H. submanca sp. nov., Oxyopes complicatus sp. nov. and O. submirabilis sp. nov. Hamataliwa subhadrae(Tikader, 1970) comb. nov. is transferred from Oxyopes Latreille, 1804. The females of Oxyopes mirabilis Zhang, 2005 and O.tenellus Song, 1991 are described for the first time. Hamadruas hieroglyphica (Thorell, 1887) and Hamataliwa subhadrae(Tikader, 1970) are newly recorded from China. The species Oxyopes bianatinus Xie & Kim, 1996 is considered a junior syn-onym of Oxyopes fujianicus Song & Zhu, 1993. Oxyopes decorosus Zhang & Zhu, 2005 is recorded from the Yunnan Province, China for the first time.